Genetic diversity among bean landraces and cultivars for agronomy traits and selection of superior parents - Godoy dos Santos, Guilherme (Revista Ciência Agronômica, 2021)
The characterization of genetic diversity in common bean genotypes for various agronomic traits enables the selectionof promising parents and the identifi cation of genotypes with high agronomic performance. The present study proposes to evaluate thegenetic diversity of common bean landraces and cultivars for 14 agronomic traits; examine the correlations between these traits; defi nepromising crosses; and select genotypes with high agronomic performance. A total of 49 common bean genotypes were evaluated in threegrowing seasons, consisting of 37 landraces and 12 common bean cultivars. Signifi cant effects of genotype × environment interactionor genotype were observed for all agronomic traits, thereby allowing the study of genetic divergence. Several plant-architecture traitswere correlated with each other, whereas grain yield was highly correlated with insertion of the last pod (r = 0.74), number of podsper plant (r = 0.74) and mass of 100 grains (r = - 0.64). The furthest-neighbor method separated the common bean genotypes intotwo groups, Mesoamerican and Andean, and mass of 100 grains showed the greatest contribution to the differentiation between thegenotypes. Tocher’s method was more informative and divided the common bean genotypes into 12 groups. The following crossesare recommended: Vagem Roxa × IPR Juriti, Vagem Roxa × Macanudo, Fepagro Triunfo × IPR Juriti, Fepagro Triunfo × Macanudo,Guapo Brilhante × IPR Juriti, and Guapo Brilhante × Macanudo. The common bean genotypes Fepagro Triunfo, IPR Juriti, GuapoBrilhante, BRS Campeiro and Vagem Roxa have high agronomic performance and should thus be selected by the breeding program.